2021
DOI: 10.3758/s13423-021-01973-2
|View full text |Cite
|
Sign up to set email alerts
|

What processes are disrupted during the attentional blink? An integrative review of event-related potential research

Abstract: Reporting the second of two targets is impaired when these appear in close succession, a phenomenon known as the attentional blink (AB). Despite decades of research, what factors limit our ability to process multiple sequentially presented events remains unclear. Specifically, two central issues remain open: does failure to report the second target (T2) reflect a structural limitation in working memory (WM) encoding or a disruption to attentional processes? And is perceptual processing of the stimulus that we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 128 publications
4
22
0
Order By: Relevance
“…Taskirrelevant perceptual learning occurs for stimuli paired with a target, but these effects are most reliable for stimuli that are presented below threshold, or outside focused attention, making them less likely to be inhibited by control mechanisms (Tsushima et al, 2008;Choi et al, 2009). It also overlaps with proposals suggesting that the attentional blink (the impaired ability to detect a target that occurs 200-500 ms after an earlier target), could reflect disruptions to control or selection mechanisms (Kawahara et al, 2006;Zivony and Lamy, 2021). In a similar way, disrupting control could also result in the inclusion of task-irrelevant information by the ABE.…”
Section: Boosting State Changes By Disrupting Top-down Controlmentioning
confidence: 85%
“…Taskirrelevant perceptual learning occurs for stimuli paired with a target, but these effects are most reliable for stimuli that are presented below threshold, or outside focused attention, making them less likely to be inhibited by control mechanisms (Tsushima et al, 2008;Choi et al, 2009). It also overlaps with proposals suggesting that the attentional blink (the impaired ability to detect a target that occurs 200-500 ms after an earlier target), could reflect disruptions to control or selection mechanisms (Kawahara et al, 2006;Zivony and Lamy, 2021). In a similar way, disrupting control could also result in the inclusion of task-irrelevant information by the ABE.…”
Section: Boosting State Changes By Disrupting Top-down Controlmentioning
confidence: 85%
“…Second, when participants are asked to identify two successive targets (T1 and T2) in the RSVP stream (Fig. 3c), the accuracy of reporting both targets is high when they appear more than half a second apart, but report accuracy for T2 is strongly impaired when it is presented within 200-500 ms after T1 (attentional blink; Raymond, Shapiro, & Arnell, 1992; see Zivony & Lamy, 2021, for a discussion of different accounts of this phenomenon).…”
Section: Evidence For the Existence Of Attentional Episodesmentioning
confidence: 99%
“…However, not all studies agree; Jiang and Chun (2001) showed that selection of T2 during the AB becomes more difficult and is subject to larger spatial distractor interference, suggesting that selection mechanisms are indeed compromised. And evidence from event-related potentials (ERP; see Zivony & Lamy, 2021, for a recent review of ERP studies of the AB) studies shows that the N2pc component (i.e., an ERP component linked to selective attention) is largely reduced during the AB (Jolicœur et al, 2006). Using a well-defined measure of selectivity (indexed by the α-parameter), Experiment 3 contributes to this discussion by showing only a small nonsignificant increase in distractor interference during the AB.…”
Section: Discussionmentioning
confidence: 99%